2020
DOI: 10.1371/journal.pone.0239282
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and ex vivo assessment of bladder hyper-permeability and using molecular targeted magnetic resonance imaging to detect claudin-2 in a mouse model for interstitial cystitis

Abstract: Objectives To determine if the URO-MCP-1 mouse model for bladder IC/BPS is associated with in vivo bladder hyper-permeability, as measured by contrast-enhanced MRI (CE-MRI), and assess whether molecular-targeted MRI (mt-MRI) can visualize in vivo claudin-2 expression as a result of bladder hyper-permeability. Interstitial cystitis/bladder pain syndrome (IC/BPS) is a chronic, painful condition of the bladder that affects primarily women. It is known that permeability plays a substantial role in IC/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Such studies could be performed using MRI and a Gd-labeled SuperGAG. 47,48 First in human clinical trials will then assess optimal dosing frequency in humans using well validated patient-reported outcomes measures (e.g., O'Leary-Sant questionnaires) 49 and bladder MRI permeability measures that can determine for how long SuperGAG provides protection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such studies could be performed using MRI and a Gd-labeled SuperGAG. 47,48 First in human clinical trials will then assess optimal dosing frequency in humans using well validated patient-reported outcomes measures (e.g., O'Leary-Sant questionnaires) 49 and bladder MRI permeability measures that can determine for how long SuperGAG provides protection.…”
Section: Discussionmentioning
confidence: 99%
“…Planned future research to take this concept to the clinic will include further optimization of SuperGAG biopolymer compositions to enhance binding to the urothelium to enhance duration of action, additional animal studies to assess improved efficacy and optimize dosing frequency to maintain impermeability in animals. Such studies could be performed using MRI and a Gd‐labeled SuperGAG 47,48 . First in human clinical trials will then assess optimal dosing frequency in humans using well validated patient‐reported outcomes measures (e.g., O’Leary‐Sant questionnaires) 49 and bladder MRI permeability measures that can determine for how long SuperGAG provides protection.…”
Section: Discussionmentioning
confidence: 99%
“…CE-MRI of BWH could therefore also be applied to assess colon–bladder crosstalk in inflammatory bowel disease (IBD) patients, as well as other inflammatory colon diseases. Additionally, we were able to demonstrate an increase in MRI SIs in the regions surrounding the dome of the bladder wall in a transgenic URO-MCP-1 mouse model for IC/BPS following intravesical lipopolysaccharide (LPS) exposure (see Figure 1 D–F where there was a significant increase in the % difference in MRI SI in the LPS group ( p < 0.001) due to leakage of Gd-DTPA) [ 39 ]. A similar CE-MRI approach to assess urothelial regeneration in rat bladders, which were augmented with permeable porcine small intestinal submucosa, was also used [ 40 ], indicating that this methodology can be expanded to other bladder conditions.…”
Section: Mri Imagingmentioning
confidence: 99%
“…Following the preclinical rat PS-induced BWH study, we then conducted a human pilot study comparing IC/BPS patients with normal individuals and clearly demonstrated the clinical feasibility of detecting BWH in IC/BPS [ 41 ]. Due to the increased thickness of the human bladder wall, BWH was detected within the bladder wall (see Figure 1 G–I where there was a significant increase in % difference in MRI SI for the IC bladders ( p < 0.001) compared to controls) [ 41 ] rather than the outside regions as seen in the preclinical models [ 28 , 38 , 39 ]. Another group used a mixture of both Gd-DTPA (Gadavist) and an iron oxide contrast agent, ferumoxytol, to further enhance bladder wall contrast in rats with induced cystitis (PS-induced) [ 42 ] and more recently in patients with IC [ 43 ].…”
Section: Mri Imagingmentioning
confidence: 99%
See 1 more Smart Citation